2011
DOI: 10.1111/j.1469-8137.2011.03962.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic reference data for systematics and phylotaxonomy of arbuscular mycorrhizal fungi from phylum to species level

Abstract: Summary Although the molecular phylogeny, evolution and biodiversity of arbuscular mycorrhizal fungi (AMF) are becoming clearer, phylotaxonomically reliable sequence data are still limited. To fill this gap, a data set allowing resolution and environmental tracing across all taxonomic levels is provided. Two overlapping nuclear DNA regions, totalling c. 3 kb, were analysed: the small subunit (SSU) rRNA gene (up to 1800 bp) and a fragment spanning c. 250 bp of the SSU rDNA, the internal transcribed spacer (ITS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
478
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(498 citation statements)
references
References 60 publications
(161 reference statements)
11
478
2
7
Order By: Relevance
“…Mycorrhizal inoculation was realized by adding Epoisses soil-based inoculum (spores, roots, and hyphae) of the AM fungus R. irregularis DAOM 197198 (Kruger et al 2012). Seedlings (three per pot) were grown for 4 weeks under controlled conditions (16 h photoperiod, 23°C/18°C day/night, 60% relative humidity, 220 μEinstein m −2 .s −1 photon flux density).…”
Section: Biological Materials and Growth Conditionsmentioning
confidence: 99%
“…Mycorrhizal inoculation was realized by adding Epoisses soil-based inoculum (spores, roots, and hyphae) of the AM fungus R. irregularis DAOM 197198 (Kruger et al 2012). Seedlings (three per pot) were grown for 4 weeks under controlled conditions (16 h photoperiod, 23°C/18°C day/night, 60% relative humidity, 220 μEinstein m −2 .s −1 photon flux density).…”
Section: Biological Materials and Growth Conditionsmentioning
confidence: 99%
“…Rhizophagus irregularis (DAOM 197198), recently reassigned from Glomus intraradices Schenck and Smith (Krüger et al 2012), was produced in monoaxenic cultures maintained on Agrobacterium rhizogenes-transformed chicory roots (Bécard and Fortin 1988) in twocompartment Petri plates, as described in Pérez-Tienda et al (2011). Plates were incubated in the dark at 24 °C until the fungal compartment, which contained a solid M medium without sucrose (M-C medium), was profusely colonized by the fungus (approximately 6 weeks).…”
Section: Biological Materialsmentioning
confidence: 99%
“…For instance, field experiments have shown that some AM fungi, such as Rhizophagus irregularis (Syn. Glomus intraradices; Krüger et al 2012), are deemed more tolerant to a high Pi concentration, while other species are absent under this nutrient condition (Verbruggen and Kiers 2010). High Pi availability enhances root growth and reduces the colonized versus non-colonized root length ratio (Smith et al 1992;Marschner 1995;.…”
Section: Introductionmentioning
confidence: 99%
“…The genus name Glomus, in particular, has been used for fungi that are so diverse that they should be in several different families. A major new molecular phylogenetic study, based on ribosomal RNA genes of almost all available AMF cultures, provides the support for a radical rationalization of AMF names [ 5]. For example, the frequently studied Glomus intraradicesDAOM197198, which was recently reidentified as G. irregulare [ 11] has now become Rhizophagus irregularis.…”
mentioning
confidence: 99%
“…AMF researchers were therefore well placed when the wave of next-generation sequencing hit environmental microbiology, and recent papers have used massive sequencing to reveal yet more diversity [15, 16 and 17]. In the light of these data, the 230 morphospecies described so far in the Glomeromycota [5] appear as a sensational underestimate.…”
mentioning
confidence: 99%